Risiko Pajak dan Penghindaran Pajak Berdampak Pada Kebangkrutan Perusahaan : Tinjauan Sistematis - illa susilawati; Memen Kustiawan; Ida Farida Adi Prawira (Jurnal Pendidikan Akuntansi (JPAK), 2022)
The study aims to explain the condition of a corporation if it performs tax evasion as to whether the company remains in good condition or bad condition. This study uses the Systematic Literature Review (SLR) method by reviewing several journals with national or international standards that have been published within a period of 10 years starting from 2013 to 2021. The results of this study suggest that tax avoidance and tax risks have no effect on company bankruptcy. This is because internal and external control of the company effectively encourages the management to make good tax plans and adherence to tax evasion, so that the policies that have been established do not adversely affect the company in the future. It is hoped that the study will further explore the relationship between tax avoidance and the deep risk of bankruptcy, by viewing more tax accounting strategies that facilitate it and make reference to future research.